2010
DOI: 10.1111/j.1460-9568.2010.07100.x
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous control of waking brain rhythms induces neuroplasticity in humans

Abstract: This study explores the possibility of noninvasively inducing long-term changes in human corticomotor excitability by means of a brain-computer interface, which enables users to exert internal control over the cortical rhythms recorded from the scalp. We demonstrate that self-regulation of electroencephalogram rhythms in quietly sitting, naive humans significantly affects the subsequent corticomotor response to transcranial magnetic stimulation, producing durable and correlated changes in neurotransmission. Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
142
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 173 publications
(157 citation statements)
references
References 59 publications
(75 reference statements)
14
142
0
1
Order By: Relevance
“…TMS pulses were applied to the motor cortex to measure motor-evoked potentials after learned self-regulation, without regulation or under other control conditions to probe for neuro plastic changes in the strength (that is, the excitability) of the corticospinal pathway. It was discovered that neurofeedback was associated with sustained (that is, lasting more than 20 min) decreases in intracortical inhibition following single 55 or repeated 56 training sessions.…”
Section: Homeostatic Plasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…TMS pulses were applied to the motor cortex to measure motor-evoked potentials after learned self-regulation, without regulation or under other control conditions to probe for neuro plastic changes in the strength (that is, the excitability) of the corticospinal pathway. It was discovered that neurofeedback was associated with sustained (that is, lasting more than 20 min) decreases in intracortical inhibition following single 55 or repeated 56 training sessions.…”
Section: Homeostatic Plasticitymentioning
confidence: 99%
“…Neurofeedback-induced neuroplasticity, in the form of cortical excitability changes, has been demonstrated in humans by using transcranial magnetic stimulation (TMS) on the trained brain region 55,56 . TMS pulses were applied to the motor cortex to measure motor-evoked potentials after learned self-regulation, without regulation or under other control conditions to probe for neuro plastic changes in the strength (that is, the excitability) of the corticospinal pathway.…”
Section: Homeostatic Plasticitymentioning
confidence: 99%
“…26 However, by observing its own dysregulated state via neurofeedback, the brain can be propelled into novel state configurations, which are susceptible to reinforcement and consolidation. 24 Ros et al 27 observed significant changes in neuronal activity following a session of neurofeedback training, which lasted for over 20 minutes. 27 Addiction patients who underwent neurofeedback training reported experiencing dysphoria when they used a substance following the treatment, indicating that the intervention may have rewired the brain's response to substance use.…”
Section: Discussionmentioning
confidence: 99%
“…These structural changes lead to behavioral modulations and they seem to be affected by diverse factors including brain pathology, aging, stress, as well as, trophic and gonadal factors (Kolb and Whishaw, 1998). Moreover, it was revealed in a recent study that the control of natural human brain using brain-computer interface (BCI) results in sustained excitability of motor cortex indicating not only that brain oscillations could mediate plasticity (Ros et al, 2010), but also that BCI methods lead to functional modulations.…”
Section: Future Outlookmentioning
confidence: 99%
“…Neurofeedback is a brainwave biofeedback technique (Hammond, 2011) based onoperant conditioning that might be a promising treatment tool to regulate brain plasticity in a natural, non-invasive and painless way (Ros et al, 2010) but it is not widely accepted due to its limited use (Dehghani-Arani et al, 2013). Demos (2005) defined neurofeedback as a therapeutic method that is designed for mind and body optimal training resulting in cognitive, physical, emotional and behavioral improvement.…”
Section: Future Outlookmentioning
confidence: 99%